PENGARUH TEAMWORK DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PERUMDA BPR MAJALENGKA - Neny Kusumadewi (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Employee performance is important for the company. Employee performance can be achieved with good teamwork and good communication. This study aims to determine how teamwork and communication influence the performance of employees at Perumda BPR Majalengka partially. This study used a survey method with a descriptive analysis approach and verification. The data collection technique used is using a questionnaire. The population in this study were employees of Perumda BPR Majalengka with a sample a 98 respondents using a saturated sampling technique (census). The measurement scale in this study uses the Likert scale. The data analysis used is the classical assumption test, multiple linear regression analysis, the coefficient of determination analysis and the feasibility test of the model. Hypothesis testing in this study uses a partial hypothesis test with the t test. Based on the results of the study, it shows that teamwork is included in the very good category, communication is in the very good category, and employee performance is in the very high category. This study shows that Teamwork and Communication have a positive and significant effect on employee performance.